ТЕОРЕТИЧНЕ ОБҐРУНТУВАННЯ ПОНЯТТЯ «МЕТОДИЧНА СИСТЕМА НАВЧАННЯ» У ПАРАДИГМІ МОВНОЇ ПІДГОТОВКИ МАЙБУТНЬОГО ВЧИТЕЛЯ УКРАЇНСЬКОЇ МОВИ ТА ЛІТЕРАТУРИ - Дружененко, Раїса (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті автор пропонує теоретичне обґрунтування поняття «методична система навчання» в аспекті мовної підготовки майбутнього вчителя-словесника. Логічною є аналітика філософської, математичної, лінгвістичної, педагогічної, дидактичної, лінгводидактичної наукової думки. Узагальнення і систематизація аналізованого наукового матеріалу дозволили спрогнозувати бачення методичної системи навчання майбутнього вчителя української мови і літератури як інтеграційної лінгводидактичної категорії, що має характер теоретичного моделювання та практичної реалізації сукупності взаємопов’язаних та взаємозумовлених елементів, компонентів, підсистем з метою отримання високих результатів у напрямі профільної мовної освіти словесника. В статье автор предлагает теоретическое обоснование понятия «методическая система обучения» в аспекте языковой подготовки будущего учителя словесности. Производится аналитика философской, математической, лингвистической, педагогической, дидактической, лингводидактической научной мысли. Обобщение и систематизация анализированного научного материала позволили спрогнозировать видение методической системы обучения языку будущего учителя украинского языка и литературы как интеграционной лингводидактической категории, которая имеет характер теоретического моделирования и практической реализации совокупности взаимосвязанных и взаимоопределяющих элементов, компонентов, подсистем для получения высоких результатов в направлении профильной языковой подготовки учителя словесности. In the article the author offers a theoretical foundation for the conception of «methodical system of education» in the aspect of language training of the future teacher of literature. The analytics of philosophical, mathematical, linguistic, pedagogical, didactic, lingvodidactical scientific thought is done. Generalization and systematization of the analyzed scientific data allowed to predict the vision of methodical language learning system of the future teacher of the Ukrainian language and literature as integration lingvodidactical category that has the character of theoretical modeling and practical implementation of a set of interrelated and inter defining elements, components, subsystems for getting high results in the direction to profiled language teacher’s training . The basic concept of the research is considered at two levels – substantive and procedural, in according to which the methodical system – this is a theoretical model, and proven technology. Characteristics and classification features of modern methodical system of language teaching were proposed. There is perspective and necessary problem of modeling and design of modern methodical system of teaching of Ukrainian language in the pedagogical universities with taking into consideration the integration framework of the linguistic sciences, language and literary cycles.